IMPROVING LEARNING OUTCOMES OF PHYSICAL EDUCATION USING MULTIMEDIA TECHNOLOGY IN 4.0 ERA - Mashari Mashari; Adi S (Acitya: Journal of Teaching and Education, 2021)
This research is based on physical education learning outcomes that are still low. The research aims to improve learning outcomes of badminton. The subjects of this study were students of class XI IPS SMAN 4 Bojonegoro. The number of samples in this study were 36 students. This study uses classroom action research with two cycles with a multimedia technology approach. Based on the results of the study before the action the average student score of 40 (not good); in the first cycle learning outcomes an average of 60 (enough); and in cycle II the average value is 80.45 (good) and classical completeness is 36 students or 100%. The use of multimedia technology has succeeded in increasing physical education learning outcomes. The latest multimedia facilities can answer problems that arise in learning. The effectiveness of multimedia learning can be seen from its tendency to attract the attention and interests of students because it combines views, sound and movement. So that learning takes place interesting and easy to remember by students.